Reduced graphene oxide–reinforced gellan gum thermoresponsive hydrogels as a myocardial tissue engineering scaffold. (July 2019) - Zargar, Seyed Mohammad; Mehdikhani, Mehdi; Rafienia, Mohammad
Myocardial infarction is one of the most prevalent diseases around the world. Cardiac tissue engineering is a new approach to repair and revive the structure and functionality of cardiac damaged tissue. In this study, gellan gum/reduced graphene oxide composite hydrogels were fabricated, characterized, and evaluated. The hydrogels were prepared using the solvent casting method and characterized via scanning electron microscopy and Fourier-transform infrared spectroscopy. Compressive mechanical analysis, injectability as well as electrical conductivity test were run. Furthermore, water swelling and degradation analyses were conducted. MTT assay was performed using rat myoblasts (H9C2) to determine the cytotoxicity of our samples. Results showed that reduced graphene oxide fillers dispersed acceptably and enhanced the compressive modulus and electrical conductivity of gellan gum hydrogels. However, in this regard, compressive strength and ductility were not significantly boosted with reduced graphene oxide addition. The water-swelling ratio (%) rised in the presence of reduced graphene oxide, whereas the degradation rate was not significantly affected by them. Meanwhile, synthesized hydrogels showed suitable injectability. MTT assay results revealed that gellan gum hydrogels containing 1% and 2% reduced graphene oxide were not cytotoxic. According to the findings, gellan gum/2% reduced graphene oxide composite hydrogel can be a promising candidate for repairing and healing infarcted myocardial tissue.